Analysis of Psychological Aspects of Taekwondo Athletes in Training Phase - Febrianty, Mona Fiametta; Purnamasari, Ira; Novian, Geraldi (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2021)
Maximum performance must be accompanied by structured and systematic training activities. In the training process, we know that four aspects must be considered, namely technical, physical, tactical, and psychological. This psychological aspect is often neglected in the training process, and Taekwondo (TKD) is no exception. A taekwondo athlete needs a variety of psychological components, including motivation, mental, self-confidence, concentration, anxiety, and others. All these psychological components must be following their respective portions, not less or even excess. The purpose of this study was to describe the psychological aspects of taekwondo athletes during training. The research method used in this study is a survey method with a research design using an ex post facto approach. The research instrument used is the Psychological Aspects in Training Phase Questionnaire (PATPQ) questionnaire which contains eight psychological aspects with 50 statements. The results showed as follows: aspects of motivation (82% = very high), mental toughness (81% = very high), self-confidence (76% = high), concentration (73% = high), fighting power (72% = high ), emotional control (66% = high) and anxiety (53% = moderate). So it can be concluded that the psychological aspects of taekwondo athletes in the training phase are still not optimal, but have led to the best performance as the training process goes on.